Managing data for the international, multicentre INTERGROWTH‐21st Project. Issue 9 (17th May 2013) - Ohuma, EO; Hoch, L; Cosgrove, C; Knight, HE; Cheikh Ismail, L; Juodvirsiene, L; Papageorghiou, AT; Al‐Jabri, H; Domingues, M; Gilli, P; Kunnawar, N; Musee, N; et al.
Abstract : The INTERGROWTH‐21 st Project data management was structured incorporating both a centralised and decentralised system for the eight study centres, which all used the same database and standardised data collection instruments, manuals and processes. Each centre was responsible for the entry and validation of their country‐specific data, which were entered onto a centralised system maintained by the Data Coordinating Unit in Oxford. A comprehensive data management system was designed to handle the very large volumes of data. It contained internal validations to prevent incorrect and inconsistent values being captured, and allowed online data entry by local Data Management Units, as well as real‐time management of recruitment and data collection by the Data Coordinating Unit in Oxford. To maintain data integrity, only the Data Coordinating Unit in Oxford had access to all the eight centres' data, which were continually monitored. All queries identified were raised with the relevant local data manager for verification and correction, if necessary. The system automatically logged an audit trail of all updates to the database with the date and name of the person who made the changes. These rigorous processes ensured that the data collected in the INTERGROWTH‐21 st Project were of exceptionally high quality.